The sellout : how three decades of Wall Street greed and government mismanagement destroyed the global financial system - Gasparino, Charles (New York, NY : Harper Business, 2009)
Offers an account of the most dramatic and anxiety-ridden era in national socioeconomic history--not merely a recounting of the collapse of Wall Street's legendary firms, but a broad examination of the people and the forces who killed Wall Street.
Fun and games -- Power and perks -- Sex, drugs, and debt -- An education in risk -- Bigger is better -- Financial renaissance -- Paying the price -- One big happy family -- Opening the floodgates -- No more Mother Merrill -- The money machine -- Perverse incentives -- Top of the world -- Cash stops flowing -- No clue -- The dancing stops -- The end begins --'There are rumoprs that you guys are in trouble' -- Free fall -- The rescue -- Bailout nation.
Includes bibliographical references and index.
Keywords: Financial crises -- United States -- History -- 21st century; Avarice -- United States -- History -- 21st century